Athletic trainers` unique clinical and teamwork skills contribute on the frontlines during the COVID-19 pandemic: A discussion paper - Breitbach, A. P.; Muchow, J. A.; Gallegos, D. F. (Journal of Interprofessional Care, 2020)
Crises such as pandemics create stresses on the health-care system that often produce innovation and changes in roles and delivery methods. In the current pandemic, and with the interruption of organized sport activities, athletic trainers have moved beyond traditional hierarchies and scopes of practice to roles that fully leverage their knowledge, skills, and abilities. Through background literature, discussion, and examples, this paper shows how the Athletic Training profession has made an impact in the response to the COVID-19 pandemic. The authors also present key questions as the health-care system moves forward through these challenges. In the future, there could be a new paradigm in the health-care system that values athletic trainers on interprofessional teams which focus on health and wellness to improve outcomes for individuals and society.